The system design of external cladding installation robot. (31st October 2020) - Yang, Dong; Li, Yongbin; Li, Tiejun; Zhang, Tian; Han, Ming; Yan, Han
In the installation process of large-scale external cladding, the labor intensity is high, and it is dangerous and hard to guarantee good construction quality. In view of these issues, this study designs a construction robot for external cladding installation, as a better solution. First, the advantages and disadvantages of the current building external cladding hanging process are discussed. The components, suitable for automatic installation, are selected to develop an automatic installation process for the building external cladding. According to the process steps and installation action flow, the installation robot is first adjusted. After the design of a step-by-step workflow of positioning and installation, a robot with a six-degree-of-freedom string-mixing mechanism is designed. Finally, a prototype of the proposed external cladding installation robot is developed, and the system is experimentally verified under simulation conditions and real operation. The test results show that the external cladding installation robot system has a strong theoretical basis. The series-parallel hybrid six-degree-of-freedom structure is reasonable, design wise. It helps to complete the automatic installation of the building external cladding and improve the automation level of large-scale plate installations.